MODEL ADAPTASI KURIKULUM ILMU PENGETAHUAN ALAM DALAM PENINGKATAN KETERAMPILAN PROSES SAINS BAGI PESERTA DIDIK AUTISM SPECTRUM DISORDER (ASD) DI KELAS INKLUSIF - Iqbal Fahri, - (2021)
Keterampilan proses sains merupakan pintu masuk keberhasilan belajar bagi peserta didik Autism Spectrum Disorder untuk memahami Ilmu Pengetahuan Alam (IPA) dalam kehidupan sehari-hari tetapi pencapaiannya masih minim dan terbatas. Riset ini dipicu oleh kondisi objektif pembelajaran yang belum menunjukkan hasil yang diharapkan. Untuk itu, riset ini bertujuan untuk mengembangkan model adaptasi kurikulum IPA dan sekaligus menguji keefektifannya dalam meningkatkan keterampilan proses sains pada peserta didik Autism Spectrum Disorder (ASD) di SMP. Masalah penelitiannya adalah Model Adaptasi Kurikulum IPA bagaimanakah yang dapat meningkatkan Keterampilan Proses Sains Peserta Didik Autism Spectrum Disorder (ASD) di Kelas Inklusif. Pemecahan masalah ini menggunakan Langkah-langkah Systems Approach Model of Educational Research and Development (R & D) sebagai payungnya. Temuannya adalah Model Adaptasi Kurikulum IPA dapat meningkatkan Keterampilan Proses Sains Peserta Didik Autism Spectrum Disorder (ASD) di kelas inklusif dalam aspek (1) pengamatan, (2) klasifikasi, (3) pengukuran, (4) komunikasi, (5) prediksi, dan (6) penarikan kesimpulan. Hasil riset ini merekomendasikan kepada guru IPA dan GPK di jenjang SMP dalam mencapai 6 (enam) aspek keterampilan proses sains bagi peserta didik ASD di kelas inklusif. Kata kunci: autism, kurikulum, sains. ABSTRACT Iqbal Fahri. (2021). Science Curriculum Adaptation Model in Improving Science Process Skills for Autism Spectrum Disorder (ASD) Students in Inclusive Classes. Dissertation. Special Education Department, School of Postgraduate Studies, Universitas Pendidikan Indonesia. Science process skills are the entrance to successful learning for students with Autism Spectrum Disorder to understand science in everyday life but their achievements are still minimal and limited. This research is triggered by the objective conditions of learning that have not shown the expected results. For this reason, this research aims to develop an adaptation model for the science curriculum and at the same time test its effectiveness in improving science process skills for students with Autism Spectrum Disorder (ASD) in junior high school. The research problem is how the Science Curriculum Adaptation Model can improve the Science Process Skills of students with Autism Spectrum Disorder (ASD) in the inclusive class. Solving this problem uses the Systems Approach Model of Educational Research and Development (R & D) steps as an umbrella. The finding is that the Science Curriculum Adaptation Model can improve the science process skills of students with Autism Spectrum Disorder (ASD) in inclusive classes in the aspects of (1) observation, (2) classification, (3) measurement, (4) communication, (5) prediction, and (6) drawing conclusions. The results of this research recommend science and GPK teachers at the junior high school to achieve 6 (six) aspects of science process skills for students with ASD in inclusive classes. Keywords: autism, curriculum, science